Decision Support Model with TreeSoft Set for Assessment of Coupled and Coordinated Development of Digital Transportation Technology and Industry - 10.5281/zenodo.15009416; Jie Liu; Jianchang Huang (Neutrosophic Sets and Systems)
The integration of digital transportation technology and the transportation industry has become a crucial factor in shaping modern mobility systems, enhancing operational efficiency, and promoting sustainability. This study evaluates the coupled and coordinated development of digital transportation innovations. Using multi-criteria decision-making (MCDM) methodologies, this research assesses key factors using BWM to compute the criteria weights. The MOOSRA method is used to rank the alternatives. This study uses the TreeSoft set to divide the criteria and sub criteria as set of levels and in each level, we compute the criteria weights. A case study with five criteria and different sub criteria with seven alternatives is conducted in this study. We conducted sensitivity analysis by using different criteria weights. This evaluation provides a systematic framework for decision-makers to optimize digital transportation strategies, ensuring a harmonized, resilient, and future-ready transportation ecosystem.